Quarantine Victors: Lived Experiences of Hospitalized COVID-19 Survivors - Joshua A. Rillo; Trisha Mae E. Uy; Carmella D. Macapagal; Ma. Chretienne R. Mariano; Michaela F. Melosantos; Cherizza Mae D. Villena; Emily A. Flores; Zuzette B. Catabona (UM Purwokerto Press, 2021)
The real-life experiences of the COVID-19 survivors during their admission to COVID facilities and their well-being during the COVID-19 phenomena are largely neglected. Given this, the study aimed to explore the experiences and grieving process of the COVID-19 survivors during and after their admission to the COVID facility. This study utilized the qualitative interpretative phenomenological design and used both the purposive and snowball sampling techniques to gather nine participants. A semi-structured interview guide developed by the researchers were used to gather data conducted online. Five themes and fifteen categories were extracted; the major themes were physiological experiences, psychological-emotional experiences, coping mechanisms, life after isolation, and stigma and discrimination. The findings revealed that the participants during the infection experienced both physiological and psychological-emotional experiences that varies based on the patient's health status and comorbidities. After the infection, the participants were relieved since they could return to their everyday lives and demonstrate a sense of growth to increase awareness to maintain a healthy physical body and observe precautionary measures. The strong association between the participants’ experiences and the stages of grieving has been known to be valid and relevant in this context. This study recommends that COVID-19 patients be given a holistic approach throughout and after their illness recovery, as this can increase their responsiveness to treatment and their overall well-being.